2013
DOI: 10.1071/sr12359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long-term wheat production management practices on soil acidity, phosphorus and some micronutrients in a semi-arid Plinthosol

Abstract: Farmers continuously remove crop residues for use as building materials, fuel and animal feed or bedding as well as to avoid difficulties during tillage operations. Therefore, demonstrations of the benefits of recycling crop residues are necessary. The aim with this study was to evaluate the influence of different wheat production management practices on acidity and some essential nutrients from a long-term trial on a Plinthosol in semi-arid South Africa. The trial was set up in 1979, and since then two method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…The tillage system has only a reduced effect on soil available Mn, with most part of significant differences being favourable to CT. Our results were partially consistent with those of some authors that reported either no differences due to tillage (de Santiago et al, 2008;Loke et al, 2013; or higher Mn availability under CT (Houx et al, 2011;Lavado et al, 1999), but contrast with other showing the opposite tendency (Edwards et al, 1992;Franzluebbers and Hons, 1996;López-Fando and Pardo, 2009;Martín-Rueda et al, 2007). Unlike the other studied trace elements, the concentration of available Mn was stratified both under MT and (to a lesser extend) CT as also found Franzluebbers and Hons (1996) and Wright et al (2007).…”
Section: Soil Available Trace Elementssupporting
confidence: 82%
See 3 more Smart Citations
“…The tillage system has only a reduced effect on soil available Mn, with most part of significant differences being favourable to CT. Our results were partially consistent with those of some authors that reported either no differences due to tillage (de Santiago et al, 2008;Loke et al, 2013; or higher Mn availability under CT (Houx et al, 2011;Lavado et al, 1999), but contrast with other showing the opposite tendency (Edwards et al, 1992;Franzluebbers and Hons, 1996;López-Fando and Pardo, 2009;Martín-Rueda et al, 2007). Unlike the other studied trace elements, the concentration of available Mn was stratified both under MT and (to a lesser extend) CT as also found Franzluebbers and Hons (1996) and Wright et al (2007).…”
Section: Soil Available Trace Elementssupporting
confidence: 82%
“…Singularly, Zn concentrations were never higher in CT than in MT, as also found most researchers (de Santiago et al, 2008;Edwards et al, 1992;Franzluebbers and Hons, 1996;Houx et al, 2011;Loke et al, 2013;Martín-Rueda et al, 2007;Wright et al, 2007). Agreeing with Franzluebbers and Hons (1996) and Wright et al (2007), extractable Zn was greater near the soil surface and decreased with depth in both MT and CT, leading to a stratification related with (but greater than) that observed for organic C (r=0.482, P< 0.01; n=212).…”
Section: Soil Available Trace Elementsmentioning
confidence: 62%
See 2 more Smart Citations
“…However, published studies on the effect of tillage on nutrients in plants are scarce (Lavado et al, 2001, Stanislawska-Clubiak andKorzeniowska, 2009), and the few available reports showed interactions between soil and plant (Houx et al, 2011;García-Marco et al, 2014). Some authors did not find differences in micronutrient concentrations between tillage systems (Westermann and Sojka, 1996), others reported higher concentration of manganeze and zinc in reduced tillage than plough tillage -Rueda et al, 2007;Loke et al, 2013), and the opposite tendency for iron and copper (Loke et al, 2013). These contrasting results could be related to soil and plant characteristics, but also to meteorological conditions during the growing season.…”
Section: Introductionmentioning
confidence: 90%